A comprehensive review on enzymatic degradation of the organophosphate pesticide malathion in the environment. (2nd October 2019) - Kumar, Smita S.; Ghosh, Pooja; Malyan, Sandeep K.; Sharma, Jyoti; Kumar, Vivek
Abstract: A comprehensive review of available bioremediation technologies for the pesticide malathion is presented. This review article describes the usage and consequences of malathion in the environment, along with a critical discussion on modes of metabolism of malathion as a sole source of carbon, phosphorus, and sulfur for bacteria, and fungi along with the biochemical and molecular aspects involved in its biodegradation. Additionally, the recent approaches of genetic engineering are discussed for the manipulation of important enzymes and microorganisms for enhanced malathion degradation along with the challenges that lie ahead.